Gamma Oscillations in the Temporal Pole Reflect the Contribution of Approach and Avoidance Motivational Systems to the Processing of Fear and Anger Words - Santaniello, Gerardo; Ferré, Pilar; Sanchez-Carmona, Alberto; Huete-Pérez, Daniel; Albert, Jacobo; Hinojosa, José A. (Frontiers in Psychology, 2022)
Prior reports suggest that affective effects in visual word processing cannot be fully explained by a dimensional perspective of emotions based on valence and arousal. In the current study, we focused on the contribution of approach and withdrawal motivational systems that are related to different action components to the processing of emotional words. To this aim, we compared frontal alpha asymmetries and brain oscillations elicited by anger words associated with approach (fighting) motivational tendencies, and fear words that may trigger either withdrawal (escaping), approach (fighting) or no (freezing) action tendencies. The participants’ task was to make decisions about approaching or distancing from the concepts represented by words. The results of cluster-based and beamforming analyses revealed increased gamma power band synchronization for fear words relative to anger words between 725 and 750 ms, with an estimated neural origin in the temporal pole. These findings were interpreted to reflect a conflict between different action tendencies underlying the representation of fear words in semantic and emotional memories, when trying to achieve task requirements. These results are in line with the predictions made by the fear-hinders-action hypothesis. Additionally, current data highlights the contribution of motivational features to the representation and processing of emotional words.